Potency of Turmeric Extract Solution (Curcuma Longa) as on Alternative Herbal Mouthwash in Gingivitis Marginalis - Febi Magfirah; Ari Suwondo; Supriyana Supriyana; Diyah Fatmasari; Masrifan Djamil (Syntax Corporation Indonesia, 2023)
Marginal gingivitis is an inflammation of the gingiva at the margin and is the earliest stage characterized by a reddish inflammation that is not persistent but prominent in areas where bacterial plaque is concentrated. Preventive efforts to rinse mouthwash contain antibacterial, long-term use has side effects, so we need herbal ingredients that have antibacterial properties, one of which is turmeric. This researcher aims to prove the potential of turmeric extract solution (Curcuma longa) as an alternative herbal mouthwash against gingivitis marginalis. This type of research uses a Quasy experiment with a pre and post test design with a control group design. Consisting of the intervention group using turmeric extract mouthwash with a concentration of 2.5%, 5% and the control group without active ingredients, the sample consisted of 27 people gargling for 1 minute for 5 consecutive days. Index gingival examination before and after rinsing. The results of the independent t-test for reducing marginal gingivitis at concentrations of 2.5% and 5% on days 1 and 2 showed a sig value of 0.002, on day 3 the sig value was 0.004, on days 4 and 5 the sig value was 0.000 meaning that there was a significant difference in reduction of marginal gingivitis. The conclusion of this study is that herbal mouthwash is effective as an alternative to herbal mouthwash in reducing marginal gingivitis compared to formulas without active ingredients.